A numerical method for predicting the deformation of crazed laminated windows under blast loading. (1st October 2018) - Linz, Paolo Del; Liang, Xu; Hooper, Paul A.; Arora, Hari; Pascoe, Luke; Smith, David; Cormie, David; Dear, John P.
Highlights: Glazing crack pattern is used to derive a novel analytical deformation model. The results from a blast test on a large window are presented. Blast experimental results are used to verify the proposed method. Abstract: The design of laminated glazing for blast resistance is significantly complicated by the post-crack behaviour of glass layers. In this research, a novel numerical method based on a semi-analytical energy model is proposed for the post-crack behaviour of crazed panes. To achieve this, the non-homogenous glass cracks patterns observed in literature experimental and analytical work was taken into consideration. It was assumed that, after the glass crazing, further deformations would occur in the cracked edge areas, whilst the central window surface would remain largely undeformed. Therefore, different internal work expressions were formulated for each zone and were then combined in the overall model. The resulting differential equation was then solved numerically. The results obtained were compared with data from four experimental full-scale blast tests for validation. Three of these blast tests (Tests 1–3) were presented previously (Hooper et al., 2012) on 1.5 × 1.2 m laminated glazing samples made up with two 3 mm glass layers and a central 1.52 mm PVB membrane, using a 15 and 30 kg charge masses (TNT equivalent) at 13–16 m stand-off. The fourth blast test (Test 4) was conducted on a larger 3.6 × 2.0 m pane of 13.52 mm thickness, using a 100 kg charge mass (TNT equivalent) at a 17 m stand-off. All blast tests employed the Digital Image Correlation (DIC) technique to obtain 3D out-of-plane deflections and strains. The proposed analytical method reproduced the experimental deflection profiles, with the best estimates obtained for the more severe loading cases. Reaction forces were also compared with experimental estimates. The predictive ability of the proposed method could permit more accurate designs to be produced rapidly, improving structures resistance to such loadings.